Karakteristik Perkembangan Kognitif Sosial dan Moral pada Masa Remaja dan Dewasa - Sarah Simanjuntak; Ferdy Prianto Simbolon; Flora Cristiani Hutapea (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
This research aims to explain the characteristics of cognitive, social and moral development in adolescence and adulthood, by highlighting various factors that influence the dynamics of individual growth at these two stages of life. Adolescence is characterized by significant changes in abstract and logical thinking abilities, which correspond to the formal operations stage in Piaget's cognitive theory. In addition, teenagers begin to develop self-identities and build more complex social relationships. In adulthood, cognitive development shows a shift from purely logical thinking to more reflective and pragmatic thinking, which adapts to real-life challenges. This research concludes that understanding the characteristics of cognitive, social and moral development in adolescence and adulthood is very important in supporting optimal individual development. The results of this research can be a reference for educators, counselors and parents in providing guidance and support in accordance with individual development needs at each stage of life.